2018
DOI: 10.3389/fneur.2018.00818
|View full text |Cite
|
Sign up to set email alerts
|

Blind Spot for Sedentarism: Redefining the Diseasome of Physical Inactivity in View of Circadian System and the Irisin/BDNF Axis

Abstract: Introduction: The term “diseasome of physical inactivity” was coined by Pedersen to explain clustering of chronic diseases linked to physical inactivity. Accordingly, physical inactivity per se contributes to the accumulation of visceral fat, which, generates chronic low-grade systemic inflammation, contributes to emergence of chronic, non-communicable diseases. Diversity of these disorders posits the possible involvement of a supraphysiological system.Methods: Hypothesis driven literature search and deductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…Irisin can exert non-thermogenic effects on several tissues, including the liver ( Tang et al, 2016 ), central nervous system ( Ferrante et al, 2016 ; Zsuga et al, 2018 ), blood vessels ( Han et al, 2015 ), or the heart ( Xie et al, 2015 ). In mouse osteocytes, irisin acts via a subset of integrin receptor complexes, which are assembled from ITGAV and either ITGB1, ITGB3, or ITGB5 ( Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Irisin can exert non-thermogenic effects on several tissues, including the liver ( Tang et al, 2016 ), central nervous system ( Ferrante et al, 2016 ; Zsuga et al, 2018 ), blood vessels ( Han et al, 2015 ), or the heart ( Xie et al, 2015 ). In mouse osteocytes, irisin acts via a subset of integrin receptor complexes, which are assembled from ITGAV and either ITGB1, ITGB3, or ITGB5 ( Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a single injection of irisin into the third brain ventricle caused an enhanced motor activity along with a reduction of resting time in rats [ 48 ] . Moreover, it was suggested that irisin released during the exercise could mediate muscle-brain crosstalk by linking the activity and circadian rhythms, thus providing the capacity to react adaptively to the environment [ 56 ] , which is consistent with the concept of entrainment of the SCN clock by exercise, and with the proposed involvement of irisin in the mechanism of entrainment [ 11 , 15 , 56 ] .…”
Section: Irisin As An Integrator Of Photic and Non-photic Entrainmentmentioning
confidence: 53%
“…One study found that a time-restricted feeding at ZT0-4 (zeitgeber time) produced a significant long-term delay of the activity offset in mice [ 74 ] , further indicating an important role for the insulin-like growth factor 2 (IGF2)/potassium chloride cotransporter 2 (KCC2) signaling in these behavioral changes. It is also suggested that the SIRT1/PGC-1α amplifying loop is involved in the entraining effect of restricted feeding [ 56 ] , which involves the activation of PGC-1α by stimulation of free fatty acid and β-hydroxybutyrate synthesis, or SIRT1-associated modulation of the NADH/NAD + ratio [ 17 , 75 ] . It was hypothesized that PGC-1α, either by local production or by the induction of irisin expression, might increase BDNF levels to the amount sufficient for the facilitation of glutamate transmission and entrainment of the SCN clock [ 56 ] .…”
Section: Irisin As An Integrator Of Photic and Non-photic Entrainmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This could represent a great advance in the understanding of neurodegenerative diseases, such as Alzheimer's disease, and could open the door for future therapeutic approaches in the management of these disorders, leading to an improvement of brain function. 8,[62][63][64][65] Irisin has already been studied as a molecular diagnostic marker for cardiovascular diseases. Decreased circulating irisin levels are associated with increased cardiovascular risk.…”
Section: Irisin and New Associationsmentioning
confidence: 99%